The legend of Zelda : twilight princess. 4 - Himekawa, Akira; Stan!, 1964- (VIZ Media, LLC, 2018)
Link must defeat evil at every turn in his perilous quest to help Princess Zelda! Once upon a time, wizards tried to conquer the Sacred Realm of Hyrule. The Spirits of Light sealed the wizards<U+2019> power within the Shadow Crystal and banished them to the Twilight Realm beyond the Mirror of Twilight. Now, an evil menace is trying to find Midna, Princess of the Twilight Realm, and the fragments of the Shadow Crystal to gain the power to rule over both the Twilight Realm and the World of Light. Link and Midna head for Death Mountain to dispel the darkness that is plaguing the Gorons and hopefully obtain another shard of the Shadow Crystal. If they can recover the shard they<U+2019>ll only need to find one more piece of the Crystal. But their journey is far from over<U+2014>shadows are gathering at Hyrule Castle and there are still many grave dangers and terrible foes to face!